Antibody response against HERV-W env surface peptides differentiates multiple sclerosis and neuromyelitis optica spectrum disorder. Issue 4 (November 2017) - Arru, Giannina; Sechi, Elia; Mariotto, Sara; Farinazzo, Alessia; Mancinelli, Chiara; Alberti, Daniela; Ferrari, Sergio; Gajofatto, Alberto; Capra, Ruggero; Monaco, Salvatore; Deiana, Giovanni A; Caggiu, Elisa; et al.
Background: A specific humoral immune response against HERV-W envelope surface (env-su) glycoprotein antigens has been reported in serum of patients with multiple sclerosis (MS). However, it has not been evaluated to date in patients with neuromyelitis optica spectrum disorder (NMOSD). Objective: The objective of this paper is to investigate whether antibody (Ab) response against HERV-W env-su antigenic peptides differs between NMOSD and MS. Methods: Serum samples were collected from 36 patients with NMOSD, 36 patients with MS and 36 healthy control individuals (HCs). An indirect ELISA was set up to detect specific Abs against HERV-W env-su peptides. Results: Our data showed that two antigenic peptides, particularly HERV-Wenv93–108 and HERV-Wenv248–262, were statistically significantly present only in serum of MS compared to NMOSD and HCs. Thus, the specific humoral immune response against HERV-W env-su glycoprotein antigens found in MS is widely missing in NMOSD. Conclusion: Increased circulating serum levels of these HERV-W Abs may be suitable as additional biomarkers to better differentiate MS from NMOSD.